2018
DOI: 10.1080/09602011.2018.1517368
|View full text |Cite
|
Sign up to set email alerts
|

On the relation between dimensions of fatigue and depression in adolescents and young adults with acquired brain injury

Abstract: Complaints of fatigue following acquired brain injury (ABI) are often associated with depression. However, the nature of this relationship is unclear; furthermore, research among young people with ABI is limited. The objective of this cross-sectional study was (1) to investigate levels of depression in young outpatients with ABI (15-30 years old) and (2) to determine how different dimensions of fatigue relate to depression. Five dimensions of fatigue were assessed with the Multidimensional Fatigue Inventory (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 67 publications
(84 reference statements)
1
5
0
Order By: Relevance
“…The experience of fatigue is inherently subjective (Aaronson et al, 1999 ; Staub and Bogousslavsky, 2001a ), and stroke survivors’ perspectives reveal that fatigue is a heterogeneous condition with several characteristics (Eilertsen et al, 2013 ). Fatigue is a nonspecific symptom with multiple potential causes and contributing factors (Krupp, 2003 ), and it is closely related to other common post-stroke conditions such as depression (Ponchel et al, 2015 ; Douven et al, 2017 ; Dornonville de la Cour et al, 2020 ) and sleep disorders (Aarnes et al, 2020 ). Several definitions of fatigue have been proposed (both generic and disease-specific) (Aaronson et al, 1999 ; Staub and Bogousslavsky, 2001a ) without consensus on a standard definition, and various subdomains of fatigue are in use without clear terminology (Kluger et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…The experience of fatigue is inherently subjective (Aaronson et al, 1999 ; Staub and Bogousslavsky, 2001a ), and stroke survivors’ perspectives reveal that fatigue is a heterogeneous condition with several characteristics (Eilertsen et al, 2013 ). Fatigue is a nonspecific symptom with multiple potential causes and contributing factors (Krupp, 2003 ), and it is closely related to other common post-stroke conditions such as depression (Ponchel et al, 2015 ; Douven et al, 2017 ; Dornonville de la Cour et al, 2020 ) and sleep disorders (Aarnes et al, 2020 ). Several definitions of fatigue have been proposed (both generic and disease-specific) (Aaronson et al, 1999 ; Staub and Bogousslavsky, 2001a ) without consensus on a standard definition, and various subdomains of fatigue are in use without clear terminology (Kluger et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence of greater levels of fatigue in BT survivors than other pABI conditions (Brand et al, 2016; Meeske et al, 2004), possibly due to treatment factors. Importantly, fatigue following pABI interferes with daily function, academic performance, and social/school participation, and is linked to poorer health-related quality of life (HRQoL) (Berrin et al, 2007; Dornonville de la Cour et al, 2018; Goretti et al, 2012; Macartney et al, 2014). Despite this, studies of fatigue in pABI are scarce.…”
mentioning
confidence: 99%
“…Fatigue in case of major depression is associated with depressive and insomnia symptoms ( 34 ). Research by Dornonvil le De La Cour et al suggested that general fatigue, mental fatigue, and reduced motivation may be associated with depression ( 35 ). Another study found that depression was independently associated with mental fatigue, reduced motivation, physical fatigue, and reduced activity but not general fatigue ( 36 ).…”
Section: Discussionmentioning
confidence: 99%